Effects of Jet Break on Summer Precipitation in Central Asia - Mingzhen Gu; Jiali Luo; Nanxuan Jiang; Lei Wang; Zhiting Wang; Fuhai Luo; Chongyang Zhang; Xufan Xia; Jiankai Zhang (Geophysical Research Letters)
Abstract The intensity and position of the westerly jet influence precipitation in Central Asia, while the impact of its structural changes on precipitation remains underexplored. This study defines a Jet Break Index based on ERA5 reanalysis data to examine how jet break events affect summer precipitation in the region. Results show that the index, derived using relative vorticity at 200 hPa, effectively identifies jet break events. The convergence and southward strengthening of Rossby waves as they propagate into Central Asia lead to jet break and trigger tropopause folding events. As stratospheric air intrudes into the troposphere, the resulting disturbance induces ascending (descending) motion in the downstream (upstream) region and is accompanied by positive (negative) vertical moisture advection contributions, thereby enhancing (suppressing) precipitation accordingly. These findings highlight the significant impact of jet break on precipitation anomalies and its implications for forecasting over Central Asia.